THE MECHANISM OF COLCHICINE INHIBITION OF MITOSIS : I. Kinetics of Inhibition and the Binding of H(3)-Colchicine - Taylor, Edwin W. (The Rockefeller University Press, 1965)
H(3)-colchicine of high specific activity (2.5 curies per mM) was prepared in order to study the mechanism of colchicine inhibition of mitosis in cultures of human cells, strain K.B. No direct effects on the duration of the cell cycle or macromolecular synthesis were demonstrable at a concentration of colchicine which completely inhibited mitosis. The radioactive compound was bound to the cells at a rate proportional to colchicine concentration. The binding appeared to be reversible since the radioactivity of the cells reached a maximum value for a given concentration and was slowly lost after resuspension of the cells in fresh medium. A suitable exposure to colchicine produced accumulation of metaphase-blocked mitoses after the colchicine was removed from the medium. An exposure of 6 to 8 hours at 10(-7) M was sufficient to block essentially all the cells in metaphase, thus indicating that colchicine is bound to the majority of interphase cells. The data are in quantitative agreement with a mechanism involving reversible binding of colchicine to a set of cellular sites. Based on the correlation between the time of first appearance of blocked mitoses and the radioactivity per cell, it is suggested that if a critical fraction (3 to 5 per cent) of the sites are complexed, the cell is unable to form a functional mitotic spindle.